Teacher knowledge of anxiety and use of anxiety reduction strategies in the classroom. Issue 2 (18th December 2022) - Ginsburg, Golda S.; Pella, Jeffrey E.; Ogle, Robert R.; DeVito, Anneliese; Raguin, Katherine; Chan, Grace
Abstract: The current study examined elementary (or primary) school teachers' knowledge of student anxiety and evidence-based anxiety reduction strategies, whether this knowledge was associated with their use of evidence-based anxiety reduction strategies in the classroom, and correlates of teacher knowledge and use of anxiety reduction strategies in the classroom. Fifty-one volunteer elementary teachers (98% female; 98% White) participated and completed questionnaires about: themselves and work-related factors (e.g., years of teaching experience, self-efficacy), knowledge of student anxiety and anxiety treatment (e.g., core manifestations of anxiety such as physiological arousal, behavioural avoidance, and anxious thoughts), and use of anxiety reduction strategies in the classroom (e.g., relaxation strategies, encouraging the use of coping self-talk, and gradual exposure to feared situations). Results indicated that the average score on the knowledge assessment was 57% and knowledge levels were unrelated to self-reported use of anxiety reduction strategies. The most robust correlate of knowledge of anxiety and use of anxiety reduction strategies was teachers' perceived personal accomplishment. Findings suggest additional teacher training to increase knowledge about student anxiety and use of evidence-based anxiety reduction strategies in the classroom is warranted.